2021
DOI: 10.18805/ijare.a-5632
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chemical Defoliants on Chlorophyll Fluorescence, Biochemical Parameters, Yield and Fiber Quality of High Density Cotton

Abstract: Background: The Cotton growing farmers in India are facing major problem at the time of harvest due to labor shortages, asynchronized boll opening, leaf trash in the cotton, which is reducing the boll picking efficiency and fiber quality. Presently, the Indian cotton industry is moving towards mechanical harvesting by cotton harvester. Defoliation or leaf abscission is induced in cotton as a natural physiological process which usually is inadequate for a complete mechanical harvest of cotton. Defoliation befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, Karademer et al reported that defoliation is possible even when 40% of the cotton bolls were opened as they found insignificant results on seed cotton yield, ginning percentage, and fiber quality across different percentages of boll opening [14]. Although several factors affect cotton yield and fiber quality; timing of defoliation application [17], type of chemicals used [18], and spraying technologies are major factors [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, Karademer et al reported that defoliation is possible even when 40% of the cotton bolls were opened as they found insignificant results on seed cotton yield, ginning percentage, and fiber quality across different percentages of boll opening [14]. Although several factors affect cotton yield and fiber quality; timing of defoliation application [17], type of chemicals used [18], and spraying technologies are major factors [19].…”
Section: Introductionmentioning
confidence: 99%